Abundance of corn planthopper (Stenocranus pacificus) (Hemiptera: Delphacidae) and the potential natural enemies in West Sumatra, Indonesia - NOVRI NELLY; MY SYAHRAWATI; HASMIANDY HAMID (Society for Indonesian Biodiversity, 2017)
Nelly N, Syahrawati M, Hamid H. 2017. Abundance of corn planthopper (Stenocranus pacificus) (Hemiptera: Delphacidae) and the potential natural enemies in West Sumatra, Indonesia. Biodiversitas 18: 696-700. A study about the abundance of corn planthopper Stenocranus pacificus and diversity of it's potential natural enemies in West Sumatra, Indonesia was conducted from July until October 2016 in Pasaman Barat, Limapuluh Kota and Tanah Datar. The method was purposive random technique sampling. Sampling Stenocranus pacificus Kirkaldy (Hemiptera: Delphacidae) and it's potential natural enemies were collected by using a modified d-vac vacuum. The Identification was done based on morphological differences between species. The result showed that corn planthopper was found in all study location, as well as natural enemies could be found in the vegetative and generative phase of corn. The distribution pattern of corn planthopper, S. pacificus generally was aggregated, except on the vegetative phase in Pasaman Barat that classified as uniform. The natural enemies that found consist of two class (Insects and Arachnids) and three ordo (Hymenoptera, Coleoptera and Araneae). Diversity index (H) of natural enemies in Pasaman Barat is higher than Tanah Datar and Limapuluh Kota district. Evenness index at all study locations showed low value (E<1).